2022
DOI: 10.3390/v14112372
|View full text |Cite
|
Sign up to set email alerts
|

How EBV Infects: The Tropism and Underlying Molecular Mechanism for Viral Infection

Abstract: The Epstein–Barr virus (EBV) is associated with a variety of human malignancies, including Burkitt’s lymphoma, Hodgkin’s disease, nasopharyngeal carcinoma and gastric cancers. EBV infection is crucial for the oncogenesis of its host cells. The prerequisite for the establishment of infection is the virus entry. Interactions of viral membrane glycoproteins and host membrane receptors play important roles in the process of virus entry into host cells. Current studies have shown that the main tropism for EBV are B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 149 publications
1
15
0
Order By: Relevance
“…EBV has been thought to be associated with the development of several malignancies, such as Burkitt's lymphoma, Hodgkin's disease, and undifferentiated nasopharyngeal carcinoma. 179,180 Latent membrane protein 1 (LMP1), a key oncoprotein of EBV, is closely associated with various changes in EBV-associated cancers, including nasopharyngeal carcinoma (NPC). This protein might be responsible for apoptosis inhibition, cell proliferation, immortalization and transformation promotion, and metastasis of cancer cells.…”
Section: Rna-cleaving Dnazymes For Gene Therapymentioning
confidence: 99%
“…EBV has been thought to be associated with the development of several malignancies, such as Burkitt's lymphoma, Hodgkin's disease, and undifferentiated nasopharyngeal carcinoma. 179,180 Latent membrane protein 1 (LMP1), a key oncoprotein of EBV, is closely associated with various changes in EBV-associated cancers, including nasopharyngeal carcinoma (NPC). This protein might be responsible for apoptosis inhibition, cell proliferation, immortalization and transformation promotion, and metastasis of cancer cells.…”
Section: Rna-cleaving Dnazymes For Gene Therapymentioning
confidence: 99%
“…In B cells, EBV infection is mediated by gp350 and gp42, while in epithelial cells, it is mediated by gHgL. 16 Additionally, gB serves as the primary fusogen indispensable for EBV entry into host cells. 17 Previous studies have demonstrated that antibodies targeting EBV glycoproteins possessed a potent ability to neutralize EBV infection in both B cells and epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms involved in EBV attachment to host cells are diverse and complex. In B cells, EBV infection is mediated by gp350 and gp42, while in epithelial cells, it is mediated by gHgL 16 . Additionally, gB serves as the primary fusogen indispensable for EBV entry into host cells 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Envelope glycoproteins have multiple important roles (reviewed in [ 29 ]) ranging from cellular entry [ 30 ] and viral assembly [ 31 ] to immune evasion [ 32 ]. EBV glycoproteins help dictate its preferential tropism for B cells, which has important implications in generating B-cell pathologies [ 33 ].…”
Section: Introductionmentioning
confidence: 99%